MGIDI-guided multi-trait selection and diversity analysis of elite and minicore-derived blackgram genotypes in the North-Western Himalayas - Pramod Kumar Meghwal; Uttam Chandel; Nimit Kumar; Vivek Singh; Shorya Kapoor (Journal of Applied Genetics, 2026)

Morpho-molecular Characterization and Population Structure Analysis in Black Gram (Vigna mungo (L.) Hepper) Using SSR Markers - Alka Soharu; V. K. Sood; R. K. Mittal; Nimit Kumar; Chetariya C.P.; Reginah Pheirim; Priyanka Upadhyay (Plant Molecular Biology Reporter, 2025)

Unlocking genetic potential, trait associations, and molecular confirmation of bacterial wilt resistance in bell pepper - Tamanna Sood; Sonia Sood; V. K. Sood; Nimit Kumar (Molecular Biology Reports, 2025)

Harnessing genetic diversity in himalayan wheat landraces: implications for yield and resilience in breeding programs - Kulveer Singh Dhillon; Harinder K. Chaudhary; V. K. Sood; Shubham Verma; Khushwinder Kaur; Nimit Kumar (Genetic Resources and Crop Evolution, 2025)

Elucidating Morpho-Molecular Diversity in Soybean Germplasm Using SSR Markers - Ronika Thakur; Vedna Kumari; Sanjay Gupta; Rakesh Kumar Chahota; Sachiko Isobe; Kenta Shirasawa; Rajesh Vangala; Ashita Bisht; Nimit Kumar (Plant Molecular Biology Reporter, 2025)

Genetic variability and correlation studies based on diverse wheat panel for grain yield and related attributes under north-western Himalayan conditions - Anoushka Sharma; Vijay Rana; Daizy Basandrai; Sundeep Kumar; Nimit Kumar; Ankita Mohapatra; Naiya Sharma; Anish Dhiman; Akhilesh Sharma (Vegetos, 2025)

Deciphering genetic diversity and population structure of onion (Allium cepa L.) using agro-morphological and molecular markers - Shorya Kapoor; Sonia Sood; Kuldip Jayaswall; Vinod Kumar Sood; Nimit Kumar; Tamanna Sood; Deepanshu Jayaswal; Vakul Sood (Horticulture, Environment, and Biotechnology, 2025)

Harnessing Marine Open Data Science for Ocean Sustainability in Africa, South Asia, and Latin America - Paige Martin; Elizabeth Holmes; Emilio Mayorga; Joseph Ansong; Uday Bhaskar; Jorge Cornejo-Donoso; David Correa-Chilón; Richard Damoah; Denisse Fierro-Arcos; Laura Gómez-Navarro; Nimit Kumar; Aderonke Lawal-Are; et al. (Oceanography, 2025)
One of the biggest barriers to conducting ocean science around the globe is limited access to computational tools and resources, including software, computing infrastructure, and data. Open tools, such as open-source software, open data, and online computing resources, offer promising solutions toward more equitable access to scientific resources. Here, we discuss the enabling power of these tools in under-resourced and non-English speaking regions, based on experience gained in the organization of three independent programs in West African, Latin American, and Indian Ocean nations. These programs have embraced the “hackweek” learning model that bridges the gap between data science and domain applications. Hackweeks function as knowledge exchange forums and foster meaningful international and regional connections among scientists. Lessons learned across the three case studies include the importance of using open computational and data resources, tailoring programs to regional and cultural differences, and the benefits and challenges of using cloud-based infrastructure. Sharing capacity in marine open data science through the regional hackweek approach can expand the participation of more diverse scientific communities and help incorporate different perspectives and broader solutions to threats to marine ecosystems and communities.

Impact and Insights from the NF–POGO Centre of Excellence in Observational Oceanography: A Trainee Perspective - Sebastian Krieger; Kumar Nimit; Subrata Sarker; Wilfried Panassa; Lilian Krug (Oceanography, 2025)
The Nippon Foundation–Partnership for Observation of the Global Ocean (NF–POGO) Centre of Excellence (CofE, https://pogo-ocean.org/​capacity-development/centre-of-excellence/) has provided advanced training in observational oceanography since 2008. Each year, a cohort of 10 scholars is selected to participate in this 10-month postgraduate-level program, which consists of expert-led instruction and hands-on experience. The CofE targets early-career ocean professionals (ECOPs), primarily from developing economies, and addresses global disparities in oceanographic expertise and resources, offering scholars unique opportunities.

Preface: the role of space ocean science and technology towards sustainable development goal - Kumar Nimit; Nurul Hazrina Idris; Cara Wilson; Carlos Gabriel; Gad Levy; Jim Gower; Ming-An Lee; Sidhartha Sahoo; Stefano Vignudelli (International Journal of Remote Sensing, 2024)

Genetic diversity dissection and population structure analysis for augmentation of bread wheat (Triticum aestivum L.) germplasm using morpho-molecular markers - Shubham Verma; Harinder K. Chaudhary; Kritika Singh; Nimit Kumar; Kulveer Singh Dhillon; Mukul Sharma; V. K. Sood (Genetic Resources and Crop Evolution, 2024)

Morpho-molecular genetic diversity and population structure analysis to enrich core collections in tea [Camellia sinensis (L.) O. Kuntze] germplasm of Sri Lanka and India - Jeevan Dananjaya Kottawa-Arachchi; Mahasen A. B. Ranatunga; Ram Kumar Sharma; H. K. Chaudhary; Renuka N. Attanayake; A. M. T. Amarakoon; M. T. Kumudini Gunasekare; Balraj Sharma; Nimit Kumar; V. K. Sood (Genetic Resources and Crop Evolution, 2024)

Plastics in the Indian Ocean – sources, transport, distribution, and impacts - Charitha Pattiaratchi; Mirjam van der Mheen; Cathleen Schlundt; Bhavani E. Narayanaswamy; Appalanaidu Sura; Sara Hajbane; Rachel White; Nimit Kumar; Michelle Fernandes; Sarath Wijeratne (Ocean Science, 2022)
Plastic debris is the most common and exponentially increasing human pollutant in the world's ocean. The distribution and impact of plastic in the Pacific and Atlantic oceans have been the subject of many publications but not so the Indian Ocean (IO). Some of the IO rim countries have the highest population densities globally and mismanagement of plastic waste is of concern in many of these rim states. Some of the most plastic-polluted rivers empty into the IO, with all this suggesting that the IO receives a tremendous amount of plastic debris each year. However, the concentration, distribution, and impacts of plastics in the IO are poorly understood as the region is under-sampled compared to other oceans. In this review, we discuss sources and sinks, which are specific to the IO. We also discuss unique atmospheric, oceanographic, and topographic features of the IO that control plastic distribution, such as reversing wind directions due to the monsoon, fronts, and upwelling regions. We identify hotspots of possible plastic accumulation in the IO, which differ between the two hemispheres. In the southern IO, plastics accumulate in a garbage patch in the subtropical gyre. However, this garbage patch is not well defined, and plastics may leak into the southern Atlantic or the Pacific Ocean. There is no subtropical gyre and associated garbage in the northern IO due to the presence of landmasses. Instead, the majority of buoyant plastics most likely end up on coastlines. Finally, we identify the vast knowledge gaps concerning plastics in the IO and point to the most pressing topics for future investigation.

Improving landings forecasts using environmental covariates: A case study on the Indian oil sardine ( Sardinella longiceps ) - Elizabeth Eli Holmes; Smitha BR; Kumar Nimit; Sourav Maity; David M. Checkley; Mark L. Wells; Vera L. Trainer (Fisheries Oceanography, 2021)
Commercial landings of sardines are known to show strong year‐to‐year fluctuations. A key driver is thought to be environmental variability, to which small forage fish are especially sensitive. We examined the utility of including environmental covariates in forecasts for landings of the Indian oil sardine using a long‐term time series of quarterly catches. Potentially influential variables examined included precipitation, upwelling intensity, sea surface temperature (SST), and chlorophyll‐a concentration. All of these have been shown to be important for oil sardine growth and survival, spawning and/or movement into the nearshore fishing regions. However, improving out‐of‐sample landings forecasts using environmental covariates has often proven elusive. We tested the inclusion of environmental covariates in forecast models using generalized additive models, which allow for non‐linear responses, and dynamic linear models, which allow for time‐varying responses. Only two environmental covariates improved out‐of‐sample prediction: the 2.5‐year average regional SST and precipitation over land during June–July. The most significant improvement was with the SST covariate and post‐monsoon landings with a 19%–22% reduction in mean‐squared prediction error. Models with the second best covariate, monsoon precipitation over land, provided a 4%–8% reduction in prediction error. We also tested large‐scale ocean climate teleconnection indices. One, an index of the Atlantic Multidecadal Oscillation, also improved out‐of‐sample predictions similarly to the multiyear average regional SST. The earth's changing climate is associated with both rapid warming in the Western Indian Ocean and changes to monsoon rainfall patterns. Our work highlights these as key variables that can improve forecasting of oil sardine landings.

Professor Trevor Platt, FRS, FRSC (1942-2020) – A heartfelt tribute - Aneesh A. Lotliker; Arvind Singh; Nimit Kumar; Rajdeep Roy; Ravidas K. Naik; Satya Prakash (International Journal of Remote Sensing, 2020)

Preface: Interdisciplinary multi-sensor studies of the Pacific and Indian Oceans - Gad Levy; Nimit Kumar; Stefano Vigundelli; Jim Gower (International Journal of Remote Sensing, 2020)

Oceanographic preferences of yellowfin tuna ( Thunnus albacares ) in warm stratified oceans: A remote sensing approach - Kumar Nimit; Nagaraja Kumar Masuluri; Aaron M. Berger; Rose P. Bright; Satya Prakash; Udayabhaskar TVS; Srinivasa Kumar T; Prathibha Rohit; Tiburtius A; Shubhadeep Ghosh; Sijo P. Varghese (International Journal of Remote Sensing, 2020)

Satellite telemetry of Yellowfin tuna feeding migration: a case study in southwestern Bay of Bengal - Rose Bright; Naga Swetha; Sanjiba Kumar Baliarsingh; Kumar Nimit; Nagaraja Kumar M; Srinivasa Kumar T; Rashmin Dwivedi; Satheesh Chandra Shenoi (Marine Geodesy, 2017)

Validation of MERIS sensor’s CoastColour algorithm for waters off the west coast of India - Kumar Nimit; Aneesh Lotlikar; T. Srinivasa Kumar (International Journal of Remote Sensing, 2016)